Ecologia e conservação de cavernas no eixo Centro-norte de Minas Gerais - Rabelo, Lucas Mendes (2016)
Caves are generally simplified environments, with stable climatic characteristics and a high level of endemisms. They are also important laboratories for researches of several science branches. Due to their frequent association with rocks of high economic value, those environments have been strongly threatened. Developing countries often have their natural landscapes replaced by activities that support developmental demands, which are usually harmful to caves. Studies in neotropical caves started late, so their patterns and tendencies are still largely unknown. In order to analyze the relationship between cave fauna and the subterranean environment and outline conservation strategies, the invertebrate communities of 51 caves of central and northern Minas Gerais state, Brazil, were sampled. Altogether, 1523 species were found, which belong to 17 classes, 47 orders and at least 193 families. The mean total species richness was 61.2 (sd = 30.6) and the mean troglobitic richness was 2.7 (sd = 2.5). The richness was positively related to the cave size, number of entrances and presence of water. The similarity was, in general, more related to the geographic distance between the caves. However, caves with water bodies are more similar to each other when compared to the other nearby caves. The fauna associated to the caves was highly correlated to the general Brazilian fauna, showing that in megadiverse regions, the number of species capable to trespass environmental and biological cave filters is high. Furthermore, almost all the groups with troglobitic representatives have levels of richness above the expected for subterranean environments, probably a result of the pre-adaptation to such environments. Despite the peculiarities of the subterranean fauna, its valuable ecosystem services and importance for the hydrological cycle of the surrounding landscape, caves have being threatened by the continuous transformation of the natural landscapes to support the social and economic development. For this reason, several conservation indices were created for caves over the last few years to rank the caves by their need of a conservationist intervention. After calculating the vulnerability level of each inventoried cave, the creation of conservation unities was recommended for the municipalities Luislândia and Coraçâo de Jesus, besides other conservation measures for other 11 caves classified as extremely high vulnerable according to the Cave Conservation Priority Index - CCPi. When comparing the three latest indices developed for the conservation of speleological patrimony, CCPi stood out as the most appropriate to evaluate the threat status and biological importance of tropical caves.